Rhopalum (Lathroropalum) creutzburgi spec. nov. from Nepal (Hymenoptera, Crabronidae). - Jacobs, Hans-Joachim (Contributions to Entomology = Beiträge zur Entomologie, 2016)
Rhopalum (Latrorhopalum) creutzburgi spec. nov. from Nepal is described. Diagnostic characters for determination of the five other species inhabiting the Asian mainland are presented. Keywords Rhopalum, Latrorhopalum, Nepal. Nomenclatural Acts creutzburgi Jacobs, 2016 (Rhopalum (Latrorhopalum)), spec. n. nursei Jacobs, 2016 (Rhopalum (Latrorhopalum)), nom. n. of Crabro petiolatus Nurse, 1902, nec Crabro petiolatus Panzer, 1797, a synonym of Mellinus crabroneus (Thunberg, 1791)